Appropriate technologies and the geosocial evolution of informal, small-scale gold mining in Madre de Dios, Peru. (December 2022) - Leiva, Jimena Díaz
Highlights: Technological choice in artisanal and small-scale gold mining is driven by the confluence of multiple social and geological factors. In Madre de Dios, Peru – gold extraction and processing technologies have evolved over time. Extraction technologies are locally-appropriate given different geological and sociopolitical circumstances. Flexible governance approaches are needed to better fit the reality of a socioeconomically differentiated and heterogeneous small-scale mining population. Abstract: This article examines the evolution of gold extraction and processing technologies used in artisanal and small-scale gold mining (ASGM) in the Amazonian region of Madre de Dios, Peru. Beyond demonstrating a historical evolution in technologies, I discuss how differentiation in gold production practices has important implications for the governance of gold mining. Proposals by policymakers to reform ASGM into a more environmentally sustainable sector often obscure the differences in gold production practices within particular mining localities. A common intervention is aimed at replacing certain technologies like mercury amalgamation – commonly used in ASGM - with alternative technologies. However, as I argue in this article, the promise of cleaner gold production through adoption of alternative technologies ultimately fails to recognize how and why diverse modalities of gold production have evolved over time. I demonstrate how in Madre de Dios, diverse gold production modalities have evolved as a response to site-specific geological conditions, differences in miners' access to capital, and a changing socio-political landscape. Putting my findings into conversation with current policy proposals, I argue that flexible governance approaches that account for heterogeneity in gold production practices and socioeconomic differentiation amongst operators, are more likely to succeed than one size fits all approaches.